2019
DOI: 10.7717/peerj.7069
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body weight gain on hepatic metabolism and hepatic inflammatory cytokines in comparison of Shetland pony geldings and Warmblood horse geldings

Abstract: Background Non-alcoholic fatty liver disease is known as determining part of human obesity. The impact of body weight (BW) gain on liver metabolism has not been extensively investigated yet. Objectives To investigate hepatic alterations caused by increasing BW in ponies and horses. Animals A total of 19 non-obese equines (10 Shetland ponies, geldings; nine Warmblood horses, geldings). Methods Animals received 200% of their metabolizable maintenance energy requirements for 2 years. Serum alkaline phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…After BW gain LPL mRNA levels were higher in AT of horses compared to ponies. In another part of this study we found higher LPL mRNA abundance in liver tissue in the same ponies compared to horses at t2 [54]. It can be speculated that the horses still had the capacity to store fatty acids in AT whereas ponies already started to store fatty acids in ectopic tissues like the liver.…”
Section: Discussionsupporting
confidence: 48%
“…After BW gain LPL mRNA levels were higher in AT of horses compared to ponies. In another part of this study we found higher LPL mRNA abundance in liver tissue in the same ponies compared to horses at t2 [54]. It can be speculated that the horses still had the capacity to store fatty acids in AT whereas ponies already started to store fatty acids in ectopic tissues like the liver.…”
Section: Discussionsupporting
confidence: 48%
“…The hepatic lipidosis observed in the Miniature Horse is likely associated with anorexia [10,18]. Liver dysfunction and failure have been reported in ECoV before and may result from endotoxemia and/or bacteremia secondary to gastrointestinal translocation [2,4,7].…”
Section: Discussionmentioning
confidence: 98%
“…In ponies receiving 200% of their maintenance metabolizable energy requirement for 2 years, Schedlbauer et al [ 33 ] found a 6.2-fold increase in ALP and a 2.3-fold increase in GGT over normal values. Serum GLDH activities in ponies were 2.4 times higher than the upper reference range, which is normally 8.9 U/L [ 34 ].…”
Section: Hepatic Enzymes Related To Hepatic Diseasementioning
confidence: 99%